2022
DOI: 10.21203/rs.3.rs-1961934/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of knowledge, attitude and anxiety in Kurdistan-region of Iraqi population during the monkeypox outbreak in 2022

Abstract: On July 23, the WHO declared the rapidly spreading monkeypox epidemic a Public Health Emergency of International Concern (PHEIC). This study attempted to assess the knowledge, attitude, and anxiety levels of the general population during the monkeypox outbreak. An online cross-sectional survey was conducted during the period July 27 and July 30, 2022, using a convenience sampling method. The questionnaire was adapted and developed after an in-depth review of the previous studies. A total of 510 respondents par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…A recent HMPX KAP study by Matteo Riccò et al reported similar low levels of knowledge among Italian physicians [ 29 ]. Low levels of HMPX knowledge were also reported among the general public in Saudi Arabia, Lebanon and Kurdistan region of Iraq [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent HMPX KAP study by Matteo Riccò et al reported similar low levels of knowledge among Italian physicians [ 29 ]. Low levels of HMPX knowledge were also reported among the general public in Saudi Arabia, Lebanon and Kurdistan region of Iraq [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This inference is consistent with other recent research that revealed that people generally in Saudi Arabia, Bangladesh, and the Kurdistan region of Iraq had little knowledge of MPXV. 16,36,37 As MPXV is endemic in tropical rainforest regions, Pakistan lies in a temperate climate zone and there has been no previous exposure to the disease in the country, rendering the disease unknown among the general population. 12,38 The majority were unaware of the origin of MPXV in the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, no psychological symptoms were measured in any of these investigations because they did not use reliable instruments. Further evidence from a cross-sectional survey conducted in Iraq indicates that the public at large is experiencing anxiety in light of the ongoing monkeypox epidemic [ 4 ].…”
mentioning
confidence: 99%